Answer:
it is 10 d a d a p a p a
Step-by-step explanation:
Answer:
6(3) - 4 + (3)^2
Explanation:
We will do this on two steps:
1- get g(x)-f(x)
2- substitute with x = 3
Step 1:
f(x) = 4-x^2
g(x) 6x
g(x) - f(x) = 6x - (4 - x^2)
= 6x - 4 + x^2
Step 2:
Substitute with x = 3 as follows:
g(x) - f(x) at x = 3 is:
6(3) - 4 + (3)^2
Hope this helps :)
P(7,6), Q(1,6), R(4,2)
We have PQ parallel to the x axis. We'll call that the base,
b = 7 - 1 = 6
The altitude is then the y difference h = 6 - 2 = 4
The area is
Answer: 12 square units
In general we can use the shoelace formula for the area of any polygon given coordinates. We write the points like this:
(7,6), (1,6), (4,2)
(1,6), (4,2), (7,6)
The area is then half the absolute value of the sum of the cross products:
Answer:
1
Step-by-step explanation:
Absolute value means take what is inside and make it positive
|5| - |-4|
5 - 4
1
Answer:
8
Step-by-step explanation:
logic